(untitled) (Ius Novum, 2024)
This study focuses on the issue of evidentiary proceedings before the appellate court in Polish criminal procedure. As a result of the considerations undertaken, the author expresses approval of the position of the Supreme Court, according to which the appellate court, upon finding specific content deficiencies in certain personal and non-personal evidence, is not only authorised but also obliged to conduct evidentiary proceedings autonomously. The provision of Article 452 of the Code of Criminal Procedure serves as the fundamental criterion for assessing the validity of this view. The application of the historical method in the interpretation process indicates that the repeal of the first section of Article 452 of the Code of Criminal Procedure, which previously stated that ‘the appellate court may not conduct evidentiary proceedings as to the substance of the case,’ contributed to establishing the principle of the appellate court conducting evidence hearings on the merits. The argumentation in this regard is enriched by the joint interpretation of Article 427 § 3 of the Code of Criminal Procedure in connection with Article 452 § 2 and 3 of the Code of Criminal Procedure.